Dengue Virus Detection by Serological and Molecular Method in Different Hospitals of Nepal - Shah, Yogendra; Gupta, Govind Prasad; Pandey, Kishor; Pun, Sher Bahadur; Pant, Krishna Prasad; Dhakal, Santosh; Pandey, Basu Dev (Medical Journal of Shree Birendra Hospital, 2013)
Introduction: Dengue is an emerging mosquito-borne viral disease in the world and is the serious public health problem of Nepal. Methods: This study was designed to determine sero-epidemiology of dengue virus infection during the period (June-Nov) of 2010 among suspected patients with fever visiting Koshi Zonal Hospital (KZH), Biratnagar, Narayani sub-regional Hospital (NSH), Birgunj, Sukraraj Tropical and Infectious Disease Hospital (STIDH), Kathmandu and Dhading District Hospital (DDH), Dhadingbeshi. The sero-prevalence of anti-dengue IgM antibody was determined by enzyme linked immunosorbent assay (ELISA). Results: Among 271 serum samples tested, the anti-dengue IgM positivity was 14.4%. Sero-positivity in male was 10.7% of total and that in female was 3.7%. Among different age groups, the highest positive cases 11.8% were from age group 15-50 years and found least among the age group above 50 years 0.4%. Out of 4 different hospitals, the highest positive positive cases from STIDH with 9.2% and the least positive cases were from DDH (0.4%). RT-PCR showed 4.7% positivity of 21 samples tested. Conclusions: Enzyme immunoassay and RT-PCR serological marker can be used to diagnose the acute patients of dengue during outbreaks. Medical Journal of Shree Birendra Hospital; July-December 2012/vol.11/Issue2/24-27 DOI: http://dx.doi.org/10.3126/mjsbh.v11i2.7905